Care ethics : the introduction of care as political category - Brugère, Fabienne (Ethics of care, 2019)
Carol Gilligan?s In a Different Voice (1982) demonstrated that women have another way of thinking morality than men. But Gilligan?s book was not only an argument about gender. She also contended that care ethics is an important concept that has too often been neglected. Dispositions and practices of care give rise to a new definition of social connections that takes vulnerability, dependence, and interdependence into consideration. Moreover, a politics of care can be an antidote to new forms of bureaucracy and to the privatization of public services. This book is an introduction to the ethics and politics of care from a philosophical point of view.